Cultivar response to fungicide application in relation to rice blast control, productivity and sustainability - Prabhu, Anne Sitarama; Filippi, Marta Cristina; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2003)
Four field trials were conducted, from 1995 to 1997, with the objective of studying the response of four upland cultivars to foliar fungicide application in relation to panicle blast control, grain yield and sustainability. Differential disease control and yield response of cultivars to fungicide treatment were obtained. Losses in grain yield of cultivars IAC 202, Caiapó, Rio Paranaíba and Araguaia due to panicle blast were 44.8%, 27.4%, 24.4% and 18.2%, respectively. Two applications of tricyclazole or benomyl controlled panicle blast, as indicated by lower values of disease progress curve and relative panicle blast severity, and increased grain yield of the cultivar IAC 202. The losses in 100 panicle grain weight and grain yield were significantly reduced by 22.3% and 25.1% in IAC 202 and 23.6% and 20.5% in Caiapó, respectively, with two sprays of tricyclazole. Sustainable value index for yield was maximum with two applications of tricyclazole (0.59), followed by one application at booting (0.46) and at heading (0.40) in cultivar IAC 202. Results showed no yield response of the cultivars Rio Paranaíba and Araguaia to fungicide applications for panicle blast control.